Determinants of the Turnover Intention of Construction Professionals: A Mediation Analysis - UĞURAL, MEHMET NURETTİN; Giritli, Heyecan; Urbanski, Mariusz (MDPI, 2020)
The voluntary turnover rate of qualified professionals is both a critical issue and a priority issue that affects organizations in different ways. The construction industry has a set of very specific and unique characteristics that demarcates it from all other sectors. This situation is related with strong precariousness and employee turnover, as well as the extensive practice of subcontracting. Furthermore, the construction sector, with its project-based production, is more vulnerable to voluntary turnover intention. Therefore, we aimed, in this study, to determine the key factors that contribute to the voluntary turnover intentions of qualified construction professionals. In this paper, the impact of individual-level value orientations on turnover intention in the construction settings, focusing on the mediating effect of external prestige and organizational identification, are investigated. Structural Equation Modeling (SEM) is employed to estimate the causal relationships between the turnover intention and other research variables. The analyses are based on questionnaire responses from 441 construction professionals living in Istanbul. The findings indicate that an individual difference in the self-construal is related to turnover intention indirectly by virtue of employees' perceptions of organizational prestige. Organizational identification also partially mediated the relationship between the self-construal and the turnover intention.
Keywords: Construction Project Management; Turnover Intention; Cultural Values; Mediation Analysis; Sustainability